CIBERSEGURANÇA E PROTEÇÃO DE DADOS SENSÍVEIS: UMA PROPOSTA DE EXTENSÃO DE NAVEGADOR PARA MITIGAÇÃO DE RISCOS - Abati Zanotto, Lucas; Vieira, Leandro Otávio (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
Introduction: Currently, the digital world has made data protection a challenge, with more evolved cyberattacks and user vulnerability. As the end-user is the most punished by social engineering attacks, there is a need for an extra layer of protection. This article combines the General Data Protection Law and the human factor to justify the development of an intuitive tool. The study seeks to determine if it is possible to create a web security tool that efficiently detects threats while also educating the user about privacy principles. Objective: To propose the conceptual development of a browser extension that acts as a proactive protection layer, mitigating unwanted access to malicious sites and alerting about risks in real-time. Method: The method was a three-stage bibliographic review. First, data breach reports, articles on the human factor, and works on law and technology were analyzed to contextualize the problem. Then, I defined the extension's rules, focusing on instant detection, lightness, and privacy. Lastly, the tool's idea was designed, with a multi-layered defense that uses lists of dangerous sites, analysis of suspicious patterns, and a machine learning model for new threats. Results: The results are a projection, as the study is conceptual. It is estimated that the extension could decrease clicks on malicious links by 40%, not only by blocking but also by explaining why, which helps to educate the user. In terms of performance, the projection is an imperceptible impact on page loading and low resource consumption. The proposal also fits what the LGPD requires, as the tool would work locally on the user's computer, respecting privacy and without collecting browsing data. Conclusion: The work showed that it is possible to think of an extension that joins technical protection, respect for laws, and attention to people's use. The main conclusion is that a good security tool should not only block but also teach and give autonomy to the user. By joining technology, human behavior, and legal rules, we can create a safer digital environment. With this in mind for the future is the creation of a prototype to test the projected results in practice. Keywords: Cybersecurity; Data Protection; Browser Extension.